Effect of shot peening residual stresses and surface roughness on fretting fatigue strength of Al 7075-T651. (February 2020) - Martín, Vicente; Vázquez, Jesús; Navarro, Carlos; Domínguez, Jaime
Abstract: Fretting fatigue is a surface damage phenomenon appearing in mechanical contacts subjected to time variable contact forces. Typical features of fretting fatigue include: wear, oxidation, high stress concentration and non-proportional loading. The high stresses near the surface produce a rapid initiation of cracks. Among the different fretting fatigue palliatives, one of the most common is shot peening. This treatment introduces high compressive residual stresses near the surface that retard the initiation of cracks, but it also changes the microstructure and surface roughness. These residual stresses relax with the number of loading cycles. This paper experimentally studies the influence of the residual stresses and the surface condition on fretting fatigue life. To this end, in this work it is analysed the residual stress relaxation produced in fretting fatigue tests due to cycling loading. On the other hand, the effect produced by the characteristic shot peening surface roughness, is analysed by means of a series of tests in which surface's fretting test specimens are polished. In addition, experimental results obtained with fretting fatigue test specimens having a surface roughness resembling that obtained with shot peening, but without residual stress, and tests done with shot peened contact pads, are presented. In all cases, contact surfaces and fretting cracks are analysed in order to understand its fretting fatigue behaviour. Finally, a fatigue life model previously developed by the authors, but including the residual stress relaxation, is applied to the different set of tests obtaining good results. The paper concludes that shot peening greatly increases fatigue life, mainly for high-cycle fatigue. This improvement can be explained mainly through the stress distribution, with little influence of surface roughness. Highlights: The fretting behaviour of shot peened Al 7075-T651 test specimens is experimentally analysed. The residual stability of the residual stress during fretting tests is analysed, both experimentally and numerically. A series of tests are carried out in order to study the shot peening induced surface roughness effect on fretting fatigue. A fatigue life model, incorporating the shot peening residual stresses, is used to predict fretting fatigue life in tests.